Application of Non-Blood-Derived Fluid Biopsy in Monitoring Minimal Residual Diseases of Lung Cancer - Yan, Xing; Liu, Changhong (Frontiers in Surgery, 2022)
lung cancer is one of the most fatal malignant tumors in the world, and the main reason why it is difficult to overcome is that it is diagnosed late and relapses after treatment. Minimal residual disease (MRD) is described as the presence of free circulating tumor cells or other tumor cell derivatives in the biological fluid of patients without any clinical symptoms of cancer and negative imaging examination after the treatment of primary tumors. It has been widely discussed in the medical community as a "bridgehead" of solid tumor recurrence. In view of the fact that radiology, serology (carcinoembryonic antigen or CEA) and other clinical diagnosis and treatment methods that are widely used to monitor the progress of disease recurrence have obvious time-limited and specific defects, and most of the samples of traditional liquid biopsies come from patients' blood (including plasma and serum), the low concentration of tumor markers in blood samples limits the ability of liquid biopsies to detect and warn in the early stage of cancer recurrence. Fluid biopsy monitoring through non-blood samples to evaluate the status of MRD, and then improve the postoperative individualized treatment of lung cancer patients is gradually ushering in the dawn of hope. This paper reviews the progress of several hot fluid samples (urine, saliva, sputum, pleural effusion) in promoting the detection of MRD in lung cancer, and discusses its application value in guiding the accurate treatment of lung cancer MRD.